2011
DOI: 10.1111/j.1467-9612.2010.00148.x
|View full text |Cite
|
Sign up to set email alerts
|

Syntactic Satiation and the Inversion Effect in English and SpanishWh‐Questions

Abstract: .  Both English and Spanish exhibit an inversion effect in wh‐questions: a verbal element must appear to the left of the subject. Analyses differ, however, as to whether this effect is due to similar syntactic mechanisms in the two languages or not. The phenomenon of judgment satiation, in which certain unacceptable sentence types improve upon repeated exposure, is used here to provide new evidence addressing this issue. It is shown that unacceptable wh‐questions in Spanish are susceptible to satiation, but th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
22
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 19 publications
3
22
0
Order By: Relevance
“…In keeping with previous research studies (e.g., Massey, 1977;Wohlhueter, 1966;Weigle, 1994;McNamara, 1996;Hiramatsu, 2000;Liu et al, 2004;Goodall 2011;Sprouse, 2007;Drave, 2011;Ling et al, 2014), the present study highlighted the necessity of raters' training, and the importance of assessment protocols in order to avoid test bias. This study also suggested that fatigue can endanger even highly qualified raters' judgment in that the frequency and type of their comments on rated essays would change in an unfair manner from the first to the last few scored essays.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…In keeping with previous research studies (e.g., Massey, 1977;Wohlhueter, 1966;Weigle, 1994;McNamara, 1996;Hiramatsu, 2000;Liu et al, 2004;Goodall 2011;Sprouse, 2007;Drave, 2011;Ling et al, 2014), the present study highlighted the necessity of raters' training, and the importance of assessment protocols in order to avoid test bias. This study also suggested that fatigue can endanger even highly qualified raters' judgment in that the frequency and type of their comments on rated essays would change in an unfair manner from the first to the last few scored essays.…”
Section: Discussionsupporting
confidence: 85%
“…One could mention its detailed analysis of the effect of fatigue on every type of comments as a strength of this study as opposed to rather general analysis of the effect of fatigue on scores given by raters (e.g., Guangming, Mollaun, & Xi, 2014). As another strength of this study, one could bring up its contribution to raters' writing assessment protocols in line with most recent studies (i.e., those conducted by Snyder, 2000;Sprouse, 2007;Hiramatsu, 2000;Goodall, 2011). The major findings of the present study can be summarized as follows;…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…The preverbal subject and the wh-phrase thus compete for the same position; a fronted wh-phrase makes it impossible for a subject to be preverbal, thus accounting for 16 (Groos & Bok-Bennema 1986, Goodall 1993, Zubizarreta 1998, Gutiérrez Bravo 2002. A third possibility is that sentences like 16 are allowed by the grammar, but that the intervening subject makes the filler-gap dependency created by wh-movement more difficult to process, leading to unacceptability (Goodall 2010(Goodall , 2011. This position is in line with the results from satiation mentioned above, if we assume that the satiation phenomenon observed with some sentence types reflects 'limitations of sentence processing, rather than genuine constraints of the speaker's grammatical competence' (Snyder 2000:580).…”
mentioning
confidence: 99%